Escherichia coli detoxificada como plataforma para produção de proteína recombinante A de superfície de pneumococo - Paredes, Sheyla Alexandra Hidalgo (Universidade Federal de São Carlos, 2018)
One of the main challenges in the therapeutic proteins production using Escherichia coli is to obtain a high purity product. Among the main contaminants (nucleic acids, polysaccharides and contaminating proteins) lipopolysaccharides deserve special attention, since its inflammatory action can lead to septic shock in mammals and for this reason its removal is crucial. Recently a E. coli genetically modified strain capable of producing recombinant proteins with low endotoxic response became commercially available and it is known as ClearColi. In this context, the purpose of the present study was to evaluate the pneumococcal surface protein A fragment (PspA) production in ClearColi as well as the growth and the physiological responses under different growth and induction conditions. The experiments were performed on shaker using a chemically defined medium (HDF) with glycerol as the main carbon source and lactose and IPTG, as inducers, at 37, 32 and 27 oC, using the factorial 22 design method. From the samples were determined the concentrations of biomass (DO600nm), nucleic acids (Abs260nm), polysaccharides (phenol-sulfuric method), lipopolysaccharides (KDO method) and proteins such as PspA and the contaminants (Bradford and electrophoresis followed by densitometry). Similar experiments were performed with a conventional production platform of this recombinant protein, based on E. coli BL21 (DE3), for comparison. In addition, an experiment using a stirred bioreactor was performed in the best conditions identified in the preliminary experiments on shaker. Thus, as results of the shaker experiments, ClearColi maximum specific growth rate was found to be about 25% smaller than the achieve with conventional E. coli. The highest PspA specific production was achieved using the inducer mixture at 32 ° C, being 165 ± 3 mg/gDCW for ClearColi and 221 ± 13 mg/gDCW for E. coli BL21. It was also found that the production of contaminating proteins was not influenced by any of the conditions evaluated for ClearColi, whereas for E. coli BL21 only at 32oC it was lower. The production of nucleic acids, polysaccharides and lipopolysaccharides occurred mainly during the exponential phase, for most of the studied conditions, therefore, their minimization depends on the choice of culture conditions during the exponential phase. From the bioreactor culture data a biomass yield of 0.63 gDCW/Lh and a protein yield of 81.2 mgPspA/Lh were estimated. The yields achieved with ClearColi were about 64% lower than those obtained with BL21, due to the longer cultivation time required with ClearColi. However, the detoxified strain has the advantage of achieving high PspA specific production values, as well as a low production of contaminating proteins when compared to the conventional strain. In addition, the detoxified strain produces a modified LPS, which does not cause significant pyrogenic reaction. Thus, the present study demonstrated that the endotoxin-free strain use as a platform for the production of recombinant proteins in industrial scale is technically possible and presents itself as a very interesting alternative for therapeutic proteins.
Endotoxin-free Escherichia coli as production platform of pneumococcal surface recombinant protein A
Keywords: ClearColi; E. coli detoxificada; PspA; Proteína contaminante; Lipopolissacarídeos; Indução; Temperatura; Endotoxin-free E. coli; Lipopolysaccharides; Induction; ENGENHARIAS::ENGENHARIA QUIMICA